PENGARUH KUALITAS PRODUK, KETERSEDIAAN PRODUK DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN PRODUK LULUR MANDI SUMBER AYU DI JAKARTA - B. Saragih, Charles Victor (MIX: JURNAL ILMIAH MANAJEMEN, 2015)
Abstract: This study aims to analyze the effect of product quality, product availability and lifestyle on purchase decision. Sumber Ayu Body Scrub was taken as a case study. This research is descriptive quantitative in nature. Both primary and secondary data were employed. Secondary data were taken from various sources such as journals and books. Primary data were taken using questionnaire. A total sample of 100 were obtained. The result shows that purchase decision was influenced by product quality, product availability and life style. The identical result found by previous researchers. Life style was found dominant variabel toward purchase decision. Keywords: Product Quality, Stock Availability, Life Style, Purchase Decision